Azo-Dye Eriochrome Black T Degradation by Heterogeneous Fenton-Like Reaction Using Olive Stones Activated Carbon-Fe Catalyst - Folorunso, Elizabeth Funmilayo (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Chemically activated carbon K-AC was fabricated from a by-product of olive oil production (olive stones) after chemical treatment with KOH. The as-synthesized activated carbon was then used for; (1) adsorption of an azo dye, Eriochrome black T (EBT) and (2) to prepare a heterogeneous Fenton catalyst Fe-AC, for degradation of same dye using the Fenton-like process. Evaluation of the effect of pH (2-10), temperature (20-50 °C) and contact time required for adsorption was studied while effects of hydrogen peroxide concentration, EBT concentration and time on rate of degradation of EBT was also determined. Optimum conditions for both processes are reported while kinetics of EBT adsorption and degradation was also investigated. Results from the undertaken study showed that temperature and pH had a predominant impact on the adsorption of EBT by K-AC. Also, the Langmuir isotherm equation provided a better fit to experimental data than Freundlich equation implying monolayer adsorption on surface of K-AC. Maximum adsorption capacity of K-AC at 20 °C as determined using the Langmuir isotherm was 101.01 mg/g. RL (0.54-0.92) and n (1.04) values confirmed that the adsorption process is favorable while positive enthalpy (ΔH°; 32.7 KJmol-1) and negative free energy (ΔG°; -1.07 KJmol-1) referred to an endothermic and a spontaneous adsorption process. EBT degradation increased as time and peroxide concentration increased. However, it decreased as EBT concentration increased. Overall, degradation experiments were conducted at optimum conditions (6mM H2O2 and pH 4) to evaluate catalyst degradation efficiency. It was further observed that adsorption kinetics of EBT followed pseudo second order kinetic model based on R2 values. Further analysis on the regeneration of spent Fe-AC using water indicates that catalyst degradation efficiency can be maintained even after three cycles which makes it economical to use in EBT degradation. According to results obtained in this study, both K-AC and Fe-AC can act as adsorbent and catalyst for the efficient removal of EBT dye. Keywords: Olive stones, Fenton process, Adsorption, Eriochrome black T

ÖZ: Kimyasal K-AC aktif Karbonun, zeytinyağı üretiminin yan ürünü olan zeytin çekirdekleri kullanarak, KOH kullanılarak kimyasal olarak üretildi. Sentezlenmiş aktif karbon , daha sonra belirtilen alanlarda; (1) Azo boya absorpsiyonunda (Eriochrome Black T) (EBT) (2) Fe-AC heterojen Fenton kataliz hazırlanışında, aynı boyanın degredasyonunda kullanılan Fenton-benzeri reaksiyonlarda kullanıldı. Aktif karbon’un absorpsiyonu için gerekli olan pH (2-10), sıcaklık (20-50 derece) ve temas süresi değerlendirilip, çalışıldı. Bu çalışmalar yapılırken hidrojen peroksit konsantrasyonunun, EBT konsantrasyonunun etkisi ve zamanının EBT nin degredasyonu üzerine olan etkisi belirlendi. EBT nin absorpsyon ve degredasyon kinetiği incelenirken, her iki reaksyon için geçerli olan optimal koşullar araştırılıp, raporlanmıştır. Yapılan çalışma ve elde edilen sonuçlar, EBT’nin K-AC tarafından absorpsiyonunda sıcaklık ve pH’in öne çıkan önemli faktörler olduğunu ortaya çıkarmıştır. Bunlara ek olarak, Langmuir İzoterm denklemi deneysel verilere Freundlinch denklemine göre daha uygun sonuçlar vermesi, K-AC aktif karbon yüzeyinin tek tabaka absorpsyonuna sahip olduğu göstermektedir. K-AC’nin maksimum absorpsiyon kapasitesi, 20 derece sıcaklıkta Langmuir izoterm denklemi kullanılarak bullundu, bu değer 101.01 mg/g olarak belirlendi. RL (0.54-0.92) ve n (1.04) değerleri gösteriyor ki positif entalpi (ΔH; 32.7 Kj mol-1) ve negatif serbest enerji (ΔG; -1.07 Kj mol -1) ki bunlar sırasıyla endotermik ve spontane absorpsyon reaksyonunu simgeler; tüm bunlar aktif karbonun absorpsyonu için elverişli olduğunu gösterir. Zaman ve hydrojen peroxit konsantrasyonu artıkça, EBT degradasyonu artar. Oysa, EBT konsantrasyonu artıkça , EBT degradasyonu azalır. Sonuç olarak, kataliz degradasyonunun verimini ölçmek için degradasyon deneyleri optimal koşullarda (6 mM H2O2 ve pH 4 ) uygulandı. Buna ek olarak , EBT R2 değerlerine göre EBT nin absorpsyon kinetiği, pseudo ikinci dereceden kinetik denklemine uygundur. Dahası, kullanılmış Fe-AC nin su kullanarak regenerasyonu gösteriyor ki katalizin degredasyon verimi üç döngüden sonra bile korunuyor, bu da, Fe-AC’nin EBT degredasyonu için ekonomik yönden uygun olduğunu gösteriyor. Çalışmadan elde edilen sonuçlara bakıldığında K-AC ve Fe-AC, her ikisinin de EBT boyasının verimli bir şekilde gideriminde absorban ve kataliz olarak görev yaptığı gözlenir. Anahtar Kelimeler: Fenton Reaksyonu, adsorpsiyon, zeytin çekirdeği, Eriochrome black T
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2018. Supervisor: Assoc. Prof. Dr. Mustafa Gazi.
Keywords: Chemistry; Olive stones; Fenton process; Adsorption; Eriochrome black T